ERRATUM - Łaźniewska-Piekarczyk, Beata (Journal of Civil Engineering and Management, 2016)
Erratum on the article “Incorporation of Rubber-steel Bearing Isolation in Multi-storey Building”. Journal of Civil Engineering & Management, 19(1), pp. 33-49.